Citizens' participation in petroleum revenue management in Ghana. (December 2022) - Ogbe, Michael
Highlights: Ghanaians do not know about petroleum revenue-funded projects in their localities. Ghanaians want the government to involve them in establishing priority areas, types, and locations of petroleum revenue-funded projects. Ghanaians are willing to participate in engagements on petroleum revenue-funded projects. Abstract: Many natural resource-rich developing countries have struggled economically. One of the common reasons is the lack of citizen participation in revenue management. This article responds to this concern by using an online geocoded survey to engage the public on petroleum revenue-funded projects in Ghana. It reflects critically on Ghanaians' knowledge about projects in their localities, surveys their opinions on how the government should involve the public in the projects' management, and determines their willingness to participate in engagements on the projects. The article makes three observations: First, Ghanaians do not know about petroleum revenue-funded projects in their localities. Secondly, Ghanaians want the government to involve them in selecting the projects' priority areas, types, and locations. Thirdly, Ghanaians are willing to participate in engagements on petroleum revenue-funded projects. The article concludes that petroleum revenue managers in Ghana should expand citizen engagement. In that regard, petroleum revenue managers should consider alternative methods such as online geocoded platforms to effectively engage citizens in managing petroleum revenue-funded projects.